OPTIMALISASI PENGGUNAAN PASIR BESI PENGGANTI AGREGAT HALUS DALAM CAMPURAN BETON MUTU TINGGI - Firjatullah Bangkit Aryoputro; Mochammad Teguh; Elvis Saputra (TEKNISIA, 2022)
Infrastructure progress needs to be supported by the development of research on construction material technology, one of which is concrete technology. With its various advantages, concrete is continuously used to solve infrastructure problems. However, it also has impact on the use of large-scale materials and has the potential to deplete natural resources if not handled properly. One material that can be used as an alternative is iron sand. Iron sand is a mineral resource with magnesium content and has characteristics as a substitute for fine aggregate in concrete mixes. This study aimed to determine the effect of iron sand as a substitute for fine aggregate in high-strength concrete mixtures. This research method was a laboratory experiment by testing the characteristics of high strength concrete, namely compressive strength, tensile strength, and modulus of elasticity. This study found that the optimum concrete compressive strength occurred in the V-02 sample with a result of 51.71 MPa from the design compressive strength (fcr) = 45 MPa. The optimum tensile strength test occurred in the V-02 sample with a result of 4.13 MPa, and the optimum elasticity modulus test occurred in the V-02 sample producing 28684.37 MPa